Correlation between Body Mass Index and Waist Circumference in Patients with Metabolic Syndrome. (4th March 2014) - Gierach, Marcin; Gierach, Joanna; Ewertowska, Marlena; Arndt, Adam; Junik, Roman
Abstract : Metabolic syndrome is defined as a group of coexisting metabolic risk factors, such as central obesity, lipid disorders, carbohydrate disorders, and arterial hypertension. According to the 2005 IDF criteria, subsequently revised in 2009, abdominal obesity is identified as the waist circumference of ≥80 cm in women and ≥94 cm in men. It is responsible for the development of insulin resistance. The aim of our study was to demonstrate a correlation between waist circumference (WC) and body mass index (BMI) in patients with metabolic syndrome in relation with hypertension, lipid disorders, and carbohydrate disorders. A cross-sectional two-site study was conducted in the Kuyavian-Pomeranian Voivodeship for 24 months. The study group consisted of 839 patients with diagnosed metabolic syndrome: 345 men (41.1%) and 494 women (58.9%) aged 32–80. In the study group, WC was found to be significantly correlated with BMI ( R = 0.78, P < 0.01). The presence of overweight in men (BMI 25, 84 kg/m 2 ) and even normal body weight in women (BMI 21, 62 kg/m 2 ) corresponds to an increased volume of visceral tissue in the abdomen. Introduction of primary prophylaxis in those people to limit the development of diabetes mellitus type 2 and cardiovascular diseases should be considered.